Pasireotide (SOM230): a novel pituitary-targeted medical therapy for the treatment of patients with Cushing's disease. Issue 5 (September 2012) - Moloney, Kelley J; Mercado, Jennifer U; Ludlam, William H; Mayberg, Marc R
Cushing's disease (CD) is a rare and debilitating condition resulting from extended exposure to excessive glucocorticoids caused by an adrenocorticotropic hormone-secreting pituitary adenoma. First-line treatment for most patients with CD is trans-sphenoidal adenomectomy. Postsurgical remission remains problematic; however, due to the difficulty of removing the tumor. Until recently, there were no approved medical treatments for Cushing's syndrome, but recent data on pasireotide (SOM230; a novel somatostatin analog) demonstrate restored hormone levels and improvements in quality of life, with a safety profile similar to that of other somatostatin analogs, except for incidence of hyperglycemia. Pasireotide represents an exciting, novel, pituitary-targeted medical therapy for patients with CD who are not surgical candidates, or for those who experience postsurgical recurrence.